Does living arrangement matter? Analyzing relations from Chinese women's perspective with cultural change - Ma, Lu; Xu, Jia (Frontiers in Sociology, 2025)
IntroductionDue to the decrease in family size and lower fertility rate in China, traditional patrilineal-centered living arrangements have become ineffective, prompting families to change them to meet their immediate and long-term care needs for families. This study examines the extent to which Chinese rural women's living arrangements improve their family relationships after marriage.MethodsThis study utilizes institutional regulatory documents at the national level and observational data from 109 semi-structured interviews with married women (aged 22-89 years), which were conducted in 2019 and 2023. Using data from interviews with married women, we examine the family structure, family expectations, and family care contribution to analyze women's different living arrangements in rural areas of southern China.ResultsIt demonstrates that women's different living arrangements have varying effect on family relationships. First, the family structure, suggesting that married women's relationship with their natal family after marriage has great impact on women's living arrangement after marriage. Second, the possibility of children inheriting the family name enhances family relations, consistent with family expectations, as the family name identifies the family members. Third, family relationships may be strengthened through providing frequent and long-term care to their natal family for married women.DiscussionWe find that the women's post-marriage living arrangements help strengthen their family relationships in a balanced manner and address unmet family care needs under the strong influence of Confucian cultural ideals. Our findings suggest that changes in living arrangements explain family relations and gender equality within the Chinese context of an aging society.